COMPARATIVE STUDY OF PSYCHOMOTOR DEVELOPMENT, FUNDAMENTAL MOVEMENTS LEVEL, BODY MASS INDEX AND FAT PERCENTAGE AMONG PUBLIC AND PRIVATE SCHOOLS STUDENTS FROM DIFFERENT REGIONS IN RIO DE JANEIRO (Fiep Bulletin - online, 2016)
The present study has investigated and compared the Psychomotor  Level and Maturation level of Fundamental Movements with Body Mass Index (BMI) and Fat Percentage of children aged  8 to 10 years old, from public and private schools in different regions in Rio de Janeiro. Four hundred students have been analysed. These students study in 10 different schools in the state. Fourty kids from each school and both genders have been analysed. Among these 10 schools, 5 were public whereas the other 5 were private.  The instruments used in this study were 1) Psychomotor Battery of Vitor da Fonseca (1995); 2) Analysis Protocol Maturation Level of Fundamental Movements proposed by Gallahue and Ozmun (2005); 3) Body Mass Index protocol proposed by the WHO (2007); 4)Considering the results revealed in the study, the groups analyzed regarding the Private Schools  stood out in relatively Psychomotor Level and Maturation Level of Fundamental Movements. However, BMI and Fat Percentage have been closer to what is regarded as the normal level. The other groups have shown a slight difference in psychomotor level, maturation of Fundamental Movements, BMI and fat percentage in comparison to one another. This is probably due to the age of the group investigated, which tends to show a stable psychomotor status condition referring to this period of development. Conclusively research suggests that the Physical Education contemplate as eyeliners goals, enabling the formation of children based on the training and optimization of psychomotor and fundamental movements structures, covering more than the motor component, but psychomotor development that involves the cognitive aspects , affective and social,  encourage healthy habits such as regular physical activity and healthy eating.
Keywords: Psychomotor Development; Fundamental Movements; Body Mass Index